Proceedings of XVIth International Workshop in Polarized Sources, Targets, and Polarimetry — PoS(PSTP2015) 2016
DOI: 10.22323/1.243.0022
|View full text |Cite
|
Sign up to set email alerts
|

DNP measurements of irradiated deuterated polyethylene

Abstract: Deuterated polyethylene samples have been prepared as polarizable target material. The paramagnetic centers necessary for the dynamic nuclear polarization process have been created by irradiation with electrons. The paramagnetic resonance from the induced centers into the samples has been studied in a conventional X-band EPR spectrometer operating at 9.35 GHz and at liquid nitrogen temperature. In a fully deuterated polyethylene sample more than 30% deuteron polarization has been achieved at dilution refrigera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Details of the ongoing research in this field can be found in the corresponding article of these proceedings [39]. The situation for radiation doped deuterated polyethylene is discussed in these proceedings as well [40].…”
Section: Pos(pstp2015)009mentioning
confidence: 99%
“…Details of the ongoing research in this field can be found in the corresponding article of these proceedings [39]. The situation for radiation doped deuterated polyethylene is discussed in these proceedings as well [40].…”
Section: Pos(pstp2015)009mentioning
confidence: 99%